Microgrids as Flexible and Network-Connected Grid Assets in Active Distribution Systems - Lei Shao; Xu Zhou; Ji Li; Hongli Liu; Xiaoqi Chen (Journal of Electrical and Computer Engineering)
The functionalities of microgrids are detailed and thereby expanded in active distribution systems. A versatile and coordinated operation among multiple microgrids is proposed to facilitate the integration of renewable energy sources (RES) in modern distribution grids. Particularly, to meet the requirements of high penetration level of renewables (e.g., photovoltaics and small hydro), more than one networked controlled microgrids are deployed simultaneously in different locations of a distribution system. Therefore, local RES can be aggregated in each microgrids. In order to satisfy the latest standards in terms of renewable energy integration (i.e., IEEE Std. 1547 Rev), an optimal operation strategy is designed to coordinate the operation of multiple microgrids. A simulation model is implemented in MATLAB to validate the proposed networked microgrids and the corresponding operation strategy.